Effectiveness of a hybrid digital substance abuse prevention approach combining e-Learning and in-person class sessions - Griffin, Kenneth W.; Williams, Christopher; Botvin, Caroline M.; Sousa, Sandra; Botvin, Gilbert J. (Frontiers in Digital Health, 2022)
Background Effective school-based programs for preventing substance abuse offer considerable public health potential. Yet limited class time and uneven implementation fidelity can be barriers to widespread adoption and high-quality implementation. A hybrid digital approach may be effective and help address these barriers. Objective To evaluate the effectiveness of a hybrid substance abuse prevention program for middle school students consisting of e-learning modules and in-person class sessions. Design Twenty-three United States (U.S.) middle schools were randomly assigned either to an intervention condition (13 schools) or a treatment-as-usual control condition (10 schools) where standard health education material was delivered. There were 1,447 participants who completed the pre-test and post-test assessments, of which 48.3% were male and 51.7% female. Intervention The hybrid digital intervention consisted of 14 brief e-learning modules and six classroom sessions adapted from an evidence-based program designed for classroom implementation to increase knowledge of adverse consequences of substance use and improve social skills, personal coping skills, and skills for resisting social influences to smoke, drink, or use drugs. Measures Participating students completed online pre-test and post-test surveys to assess substance use, knowledge, and life skills. Results There were significant reductions in substance use for the hybrid digital condition compared to the control condition as well as significant increases in health knowledge, skills knowledge, and life skills. Conclusions A hybrid digital approach to substance abuse prevention is effective and offers potential for overcoming common barriers to widespread adoption and high-quality implementation.